1988
DOI: 10.1038/bjc.1988.108
|View full text |Cite
|
Sign up to set email alerts
|

Structure and expression of oncogenes in surgical specimens of human breast carcinomas

Abstract: SummaryWe have performed an analysis of ras, c-myc, c-myb, c-erbBl and c-erbB2 onocogenes in 100 surgical samples of human breast carcinomas. No point mutations have been detected at the 12th codon of cHa-ras and c-Ki-ras in 40 and 65 breast cancer DNAs, respectively. One out of 65 samples showed a 50-fold amplification of c-Ha-ras that, however, was not overexpressed. Alterations in the structure of c-myc, c-myb c-erbBl and c-erbB2 oncogenes were sporadically observed. In 20 tumour samples, the study of expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1990
1990
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 27 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…The degree of amplification varied from 8% in some reports (19) to 47% in other reports (5). Slamon et al (1) were the first to report C-erbB-2 amplification in breast carcinoma, which they found in about 30% of the tumors.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The degree of amplification varied from 8% in some reports (19) to 47% in other reports (5). Slamon et al (1) were the first to report C-erbB-2 amplification in breast carcinoma, which they found in about 30% of the tumors.…”
Section: Discussionmentioning
confidence: 97%
“…Different groups of investigators have found that C-erbB-2 is overexpressed in some primary adenocarcinoma of the breast (1, 3, 5, 11, 13, [19][20][21][22][23][24][25][26][27]. The degree of amplification varied from 8% in some reports (19) to 47% in other reports (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(54). In human breast cancer, c-fos overexpression is associated with malignant progression (55,56). Hypoxia on the other hand is a known inducer of metastasis (57).…”
Section: C-fos Induction By Hypoxia Via Mapkmentioning
confidence: 99%
“…In a wide range of human tumors, the c fos proto-oncogene has been found expressed at high levels [15]. In human breast tumors, for example, c fos transcript is most frequently high [16], and the degree of its expression is correlated to its histological grading, with more cells positive for c fos mRNA in advanced lesions [17]. Furthermore, its expression increases in pancreatic carcinomas [18], neuromas, meningiomas [19], melanomas [20] and certain leukemias [21].…”
Section: Discussionmentioning
confidence: 99%